1995
DOI: 10.1136/bmj.311.7017.1401
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference action levels in the identification of cardiovascular risk factors: prevalence study in a random sample

Abstract: Larger waist circumference identifies people at increased cardiovascular risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
548
4
103

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 824 publications
(679 citation statements)
references
References 16 publications
24
548
4
103
Order By: Relevance
“…BMI was not independently associated with hypertension and diabetes mellitus. A study by Han et al (1995) showed clear associations between WC and hypertension and other cardiovascular risk factors but did not adjust for the overall body fatness. WC was a better predictor of diabetes mellitus (NIDDM) compared to BMI and WHR in Mexican Americans in a prospective study (Wei et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…BMI was not independently associated with hypertension and diabetes mellitus. A study by Han et al (1995) showed clear associations between WC and hypertension and other cardiovascular risk factors but did not adjust for the overall body fatness. WC was a better predictor of diabetes mellitus (NIDDM) compared to BMI and WHR in Mexican Americans in a prospective study (Wei et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Height, weight, and WC were measured by a trained nurse during the physical examination at a primary care unit or hospital clinic in charge of the national health examination programs. WC was measured between the lower margin of the last palpable rib and the top of the iliac crest, at the level of maximum circumference, using a flexible inelastic fiberglass tape with the tape parallel to the floor 22. BMI is defined as the body weight divided by the square of the body height (kg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The average of the two measurements was used in the analysis. Large waist circumference, indicative of increased CVD risk, was defined as exceeding 102 cm in men and 88 cm in women (Han et al, 1995).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Early signs of atherosclerosis and CVD risk are detectable in childhood as fatty streaks in the aorta and are related to fat mass (body mass index, BMI, kg/m 2 ), blood pressure, plasma cholesterol and triacylglycerol levels (Berenson et al, 1998). These risk factors for CVD tend to track into adulthood (Boulton, 1996), as do other modifiable risk factors such as waist circumference, Lp a concentration, hyperinsulinaemia and glucose intolerance (Han et al, 1995;Sattar et al, 1998;Clarke et al, 2002), and can be influenced by diet. As such, the diet in childhood as well as in adulthood may be a modulator of adult CVD.…”
Section: Introductionmentioning
confidence: 99%